Digesting an ancient ecosystem: Coprolites from the lower Triassic Grippia bonebed in Svalbard - Simonsen, Vanja (2024)
Five coprolite morphotypes were identified and described from the Grippia Bonebed Vikinghøgda Formation, Lower Triassic, Svalbard. The bonebed consists of disarticulated skeletal material, teeth, and coprolites. 97 coprolites were studied and sorted based on shape and inclusions. Inclusions were studied using thin sections, SEM and micro CT-scanning that gave remarkable results. The analyses revealed inclusions such as bone material, fish scales and the first documented evidence of invertebrates in the Grippia bonebed. Invertebrates include sponge spicules, a cephalopod shell fragment and a high abundance of cephalopod hooks. Possible coprolite producers are discussed and includes fish, chondrichthyians, temnospondyls, ichthyopterygians and archosauriforms. This study introduces a new method for finding cephalopod hooks in CT-scans and provides a more complete picture of the marine paleoecosystem in the Grippia bonebed, Early Triassic, Svalbard.